2015
DOI: 10.1890/es15-00229.1
|View full text |Cite
|
Sign up to set email alerts
|

Mutualism with aphids affects the trophic position, abundance of ants and herbivory along an elevational gradient

Abstract: Varied interspecific interactions have a tremendous impact on the population dynamics of related species. However, the context dependency of interspecific interactions and their ecological effects have not been well‐characterized. To understand the context dependency of ant‐aphid mutualism and the corresponding ecological effects, we explored the association of ant abundance, trophic position, and plant herbivory along an elevational gradient. We hypothesized that a higher abundance of ants would be associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…The majority (63%) of previously published studies on trends in herbivory along elevational gradients reported an overall decreasing trend with increasing elevation, while 25% reported increasing trends and the rest found no trend in herbivory (Zvereva & Kozlov, ). Two studies most closely comparable to ours showed (reporting chewing herbivory along a tropical gradient of similar length) that herbivory increased with elevation (Koptur, ; Zhang et al, ). Similarly to other studies, we focused solely on the damage caused by chewing arthropods, as one of the herbivore guilds which generally causes the highest damage to plants (Schoonhoven et al, ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The majority (63%) of previously published studies on trends in herbivory along elevational gradients reported an overall decreasing trend with increasing elevation, while 25% reported increasing trends and the rest found no trend in herbivory (Zvereva & Kozlov, ). Two studies most closely comparable to ours showed (reporting chewing herbivory along a tropical gradient of similar length) that herbivory increased with elevation (Koptur, ; Zhang et al, ). Similarly to other studies, we focused solely on the damage caused by chewing arthropods, as one of the herbivore guilds which generally causes the highest damage to plants (Schoonhoven et al, ).…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, studies along elevational gradients report a variety of patterns including decreasing (e.g., Alonso, 1999;Galen, 1990;Hülber, Haider, Hager, Dullinger, & Fiedler, 2015;Kelly, 1998;Louda, 1982;Metcalfe et al, 2014;Poveda, Martínez, Kersch-Becker, Bonilla, & Tscharntke, 2012;Suzuki, Kitayama, Aiba, Takyu, & Kikuzawa, 2013), increasing (e.g., Altmann & Claros, 2015;Hagen, Jepsen, Ims, & Yoccoz, 2007;Bito et al, 2011;Erelli, Ayres, & Eaton, 1998;Koptur, 1985;Matías & Jump, 2015;Zhang, Zhang, & Ma, 2015), or constant herbivory (Bito et al, 2011;Hódar & Zamora, 2004;Lay, Linhart, & Diggle, 2013). Generally, conclusions about arthropod herbivory along elevational gradients are far from definitive, and there is growing evidence that results are not consistent across time and space (Andrew, Roberts, & Hill, 2012;Moreira, Petry, Mooney, Rasmann, & Abdala-Roberts, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Species interactions have classically been proposed to be stronger at lower latitudes and elevations where the climate is warmer and less seasonal (Coley & Barone, ; Moreira et al, ; Schemske et al, ), but recent studies have questioned the generality of this paradigm (Moles et al, ; Moles & Ollerton, ; Zhang et al, ). Such discrepancies may arise in part because most tests for gradients in species interactions fail to adequately incorporate the ecological complexity in which the interactions are embedded (Moreira et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Species interactions have classically been proposed to be stronger at lower latitudes and elevations where the climate is warmer and less seasonal (Coley & Barone, 1996;Moreira et al, 2018;Schemske et al, 2009), but recent studies have questioned the generality of this paradigm (Moles et al, 2011;Moles & Ollerton, 2016;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…the initial number of partners at the commencement of a relationship) and biotic/abiotic environmental factors (Stadler & Dixon, 1998;Styrsky & Eubanks, 2010;Yoo & Holway, 2011;Barton & Ives, 2014;Singh et al, 2016). Thus, mutualism has a context-dependent aspect, that is, the net benefi ts for a given species depend on ecological conditions (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%